CoPtx‐loaded Zn0.5Cd0.5S nanocomposites for enhanced visible light photocatalytic H2 production. (16th March 2016) - Wang, Hanbin; Li, Yang; Shu, Dan; Chen, Xu; Liu, Xiang; Wang, Xina; Zhang, Jun; Wang, Hao
Summary: Zn0.5 Cd0.5 S solid solution, modified with bimetallic CoPt x nanoparticles, has been prepared using a two‐step organic solution method. The photocatalytic H2 production rate of CoPt x –Zn0.5 Cd0.5 S nanocomposites with different composition and percentage of CoPt x was investigated. The results showed that the 1 wt% CoPt3 –Zn0.5 Cd0.5 S sample had the best activity which was 4.7 times higher than that of pure Zn0.5 Cd0.5 S and 1.2 times higher than that of Pt–Zn0.5 Cd0.5 S for photocatalytic H2 production. The transient photocurrent response of the Zn0.5 Cd0.5 S showed an obvious increase in the current density after CoPt x loading. Electrochemical impedance spectra measurements showed that the CoPt x –Zn0.5 Cd0.5 S nanocomposites with x = 2 and 3 had lower charge transfer resistance Rt than that of Pt–Zn0.5 Cd0.5 S. The enhanced catalytic properties of the CoPt x –Zn0.5 Cd0.5 S nanocomposites are attributed to their better accumulation ability for photoexcited electrons and higher rate for charge separation and transportation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Zn0.5 Cd0.5 S solid solution modified with bimetallic CoPtx nanoparticles has been prepared using a two‐step organic solution method. The CoPtx –Zn0.5 Cd0.5 S nanocomposites showed enhanced photocatalytic activity toward H2 production by water splitting comparing with pure Zn0.5 Cd0.5 S. The highest photocatalytic activities were obtained over 1 wt% CoPt3 –Zn0.5 Cd0.5 S with a H2 production rate of 2.83 mmolh ‐1 g ‐1, which was 1.2 times higher than that of 1 wt% Pt–Cd0.5 Zn0.5 S nanocrystals.